2021
DOI: 10.3390/ijerph182413100
|View full text |Cite
|
Sign up to set email alerts
|

Do COVID-19-Related Stress, Being Overweight, and Body Dissatisfaction Contribute to More Disordered Eating in Polish Women?—A Cluster Analysis Approach

Abstract: We hypothesized that women who are overweight, experiencing COVID-19-related stress, and with high body dissatisfaction would have significantly greater disordered eating than those of healthy weight, without stress, and with low body dissatisfaction. Participants (N = 1354 women; Mage= 31.89 years, SD = 11.14) filled in the Contour Drawing Rating Scale, the Emotional Overeating Questionnaire, the Eating Motivation Survey, the Mindful Eating Questionnaire, and a COVID-19-related stress measure and sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In women, the authors found a significant self-reported increase of media pressure towards thin/low fat ideals but also an increase in appearance evaluation ( Baceviciene and Jankauskiene, 2021 ). Czepczor-Bernat et al (2021) conducted a cross-sectional study in Poland from January to March 2021. With their cluster-analysis, the authors revealed the presence of a group of women with a risky pattern of disordered eating behaviors ( N = 1,354).…”
Section: Studies On the Impact Of The Covid-19 Pandemic Context In Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…In women, the authors found a significant self-reported increase of media pressure towards thin/low fat ideals but also an increase in appearance evaluation ( Baceviciene and Jankauskiene, 2021 ). Czepczor-Bernat et al (2021) conducted a cross-sectional study in Poland from January to March 2021. With their cluster-analysis, the authors revealed the presence of a group of women with a risky pattern of disordered eating behaviors ( N = 1,354).…”
Section: Studies On the Impact Of The Covid-19 Pandemic Context In Co...mentioning
confidence: 99%
“…With their cluster-analysis, the authors revealed the presence of a group of women with a risky pattern of disordered eating behaviors ( N = 1,354). Specifically, overweight women, with high body dissatisfaction and COVID-related stress, presented higher levels of disordered eating (e.g., emotional overeating, affect regulation motive for eating; Czepczor-Bernat et al, 2021 ). In a longitudinal study conducted in Italy (T0: first lockdown in Italy, March–April 2020; T1: time of eased restriction, June 2020) among members of a Facebook online community focused on eating disorders ( N = 115), Mannino et al (2021) found that a greater fear of COVID-19 during the first lockdown was associated with self-reported time spent on Facebook, which in turn predicted disordered eating cognitions after 2 months.…”
Section: Studies On the Impact Of The Covid-19 Pandemic Context In Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, several studies stated that eating disorders occurred as a coping mechanism or emotional eating to release anxiety due to the impact of the pandemic, which is related to an increase in food intake, resulting in overweight and obesity [34]. In general, adolescents choose unhealthy foods like sugary, salty, and fast foods that contribute to weight gain [35].…”
Section: Lifestyle and Food Pattern Changesmentioning
confidence: 99%
“…Frequent occurrence of negative affect may increase risk for disordered eating through disruption to exercise routines, comparison of body image through social media and social isolation ( Rodgers et al, 2020 ). Notably, Czepczor-Bernat et al (2021) found that disordered eating was significantly higher for women who had high COVID-related stress, were overweight and had high body dissatisfaction, in comparison to women with a healthy body weight, no COVID-related stress and low body dissatisfaction. These findings are consistent with the homeostatic theory of obesity ( Marks, 2015 ) which suggests weight gain is linked to various body systems through a “circle of discontent.” For instance, the theory suggests reciprocal relationships between (1) body dissatisfaction and negative affect, (2) negative affect and consumption of energy dense foods and beverages, (3) consumption of energy dense foods and overweight/obesity, and (4) overweight/obesity and negative affect.…”
Section: Introductionmentioning
confidence: 97%